Hip 3D joint mechanics analysis of normal and obese individuals' gait - Mazlan, M.H.; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar (2011)
Previously, the study of 3D joint angle has been proven to give better interpretations on the joint and muscular activities. However, it has not been widely discovered and usually limited to normal subject and level walking activity. The inspiration of the study was based on the fact that, the obesity and staircase activity factors will significantly influence the mechanics of a joint. It has been proven significantly affected the knee rather than the hip which leading to the knee osteoarthritis disease. Moreover, since to date no experimental study has reported on hip 3D joint mechanics associating with these two factors, therefore, the analysis of hip 3D joint angle for obese and normal individuals during stair ascending activity have been proposed in order to help the hip 3D joint interpretations. Our hypothesis is that, it is hard to describe the difference of the gait strategy used between obese and normal individuals due to the effect of the mechanics adaptations of the hip joint. Therefore, with the aid of hip 3D joint angle interpretations, it is believed that these phenomena can be successfully described and investigated. The result seems to confirm that, at the late stance of stair ascending activity, the obese individuals seem to have an alternative strategy of mainly hip resistance compared to the normal' strategy of mainly hip stabilization. Otherwise, the normal and obese individuals seem to have a similar strategy of mainly hip stabilization. In addition, the obese seem to absorb or generate energy with systematically lower proportion of the 3D joint moments than normal individuals.